Digital asset valuation and cyber risk measurement : principles of cybernomics - Ruan, Keyun (Academic Press, 2019)
Digital Asset Valuation and Cyber Risk Measurement: Principles of Cybernomics is a book about the future of risk and the future of value. It examines the indispensable role of economic modeling in the future of digitization, thus providing industry professionals with the tools they need to optimize the management of financial risks associated with this megatrend. The book addresses three problem areas: the valuation of digital assets, measurement of risk exposures of digital valuables, and economic modeling for the management of such risks. Employing a pair of novel cyber risk measurement units, bitmort and hekla, the book covers areas of value, risk, control, and return, each of which are viewed from the perspective of entity (e.g., individual, organization, business), portfolio (e.g., industry sector, nation-state), and global ramifications. Establishing adequate, holistic, and statistically robust data points on the entity, portfolio, and global levels for the development of a cybernomics databank is essential for the resilience of our shared digital future. This book also argues existing economic value theories no longer apply to the digital era due to the unique characteristics of digital assets. It introduces six laws of digital theory of value, with the aim to adapt economic value theories to the digital and machine era.